Familial 46, XY Disorder of Sexual Development identified in a Ph+BCR::ABL1P210+ Acute Lymphoblastic Leukemia septuagenarian female with RCBTB2::LPAR6 fusion gene: a case report - Wang, Lingling; Xi, Conglin; Zheng, Xinyu; Huang, Yongfen; Xu, Hao; Miao, Yuqing; Cheng, Yuexin (Frontiers in Oncology, 2024)
Background Familial 46, XY Disorder of Sexual Development (DSD) was discovered in a Ph+, BCR::ABL1P210+ Acute Lymphoblastic Leukemia (ALL) female with RCBTB2::LPAR6 fusion gene. Siblings developing 46, XY DSD are extremely rare. Patients with 46, XY DSD have much higher rates of gonadal cancers. Nevertheless, the incidence of hematologic malignancies in patients with DSDs has received little attention. RCBTB2::LPAR6 is a rarely reported fusion gene in ALL. Case presentation Herein, we report a rare case of a newly diagnosed Ph+, BCR::ABL1P210+ ALL patient who was 77 years old and female by social sex. Whole Exome Sequencing (WES) and RNA sequencing revealed TET2 and NF1 mutations in addition to a rarely reported RCBTB2::LPAR6 fusion gene and 17 other genes with uncertain clinical significance. The patient was surprisingly found to have a male karyotype. On ultrasound, neither the uterus nor the ovaries were discernible. A detailed family and marital history revealed that the patient had undergone surgery at an early age for an unexplained inguinal mass. She had slow pubertal development, scanty menstruation, and few overtly feminine characteristics. She had three marriages, but none succeeded in getting pregnant. The patient had never sought therapy for infertility due to the inaccessibility of medical treatment and a lack of medical knowledge. Her sister, 73 years old and female by social sex, who had amenorrhea in adolescence and was unable to conceive, had the same experience. To our surprise, she also had a male karyotype. Conclusions Due to the absence of long-term social attention and follow-up, studies on the incidence of hematologic malignancies in patients with 46, XY DSD are incredibly uncommon. Siblings developing 46, XY DSD is extremely rare. We report the oldest patient diagnosed with 46, XY DSD. There have not yet been any reports of familial 46, XY DSD with a concurrent diagnosis of Ph+BCR::ABL1P210+ALL with a rarely reported RCBTB2::LPAR6 fusion gene.